Upaya Guru PAI Menciptakan Suasana Pembelajaran yang Efektif - Hadi Saputra Panggabean; Nida Ul Hasanah; Saffana Ulfia; Sri Devi Hardiyanti; Putri Widia Astuti; Septianingsih; Elsya Fitri (Medan Resource Center, 2021)
In learning students often experience boredom, teachers must be able to create an effective learning atmosphere for students with various methods. Schools as places of learning must also be able to create a good atmosphere especially in the classroom. However, sometimes in teaching and learning activities in schools, there are often problems related to learning experienced by these students. The problem is influenced by internal factors (which come from within the students themselves) and also external factors (which come from outside). One of the internal factors is the boredom experienced by students while studying. A teacher who can create an effective learning atmosphere for students in order to achieve learning. The essence of effective learning is a teaching and learning process that is not only focused on the results achieved by students, but how an effective learning process is able to provide good understanding, intelligence, perseverance, and provide behavior and apply it in their lives.